Effect of newborn gender on placental histopathology and perinatal outcome in singleton live births following IVF. Issue 5 (November 2020) - Volodarsky-Perel, Alexander; Nu, Tuyet Nhung Ton; Buckett, William; Machado-Gedeon, Alexandre; Cui, Yiming; Shaul, Jonathan; Dahan, Michael H
Abstract: Research question: Does newborn gender affect placental histopathology pattern and perinatal outcome in singleton live births following IVF treatment? Design: Retrospective cohort study evaluating data of all live births from one academic tertiary hospital following IVF treatment during 2009–2017. All patients had placentas sent for pathological evaluation irrelevant of maternal and fetal complications status. Exclusion criteria were abnormal uterine cavity findings, previous uterine surgery, in-vitro maturation cycles, gestational carrier cycles, oocyte recipient cycles, preimplantation genetic diagnosis cycles and multiple pregnancies. The primary outcomes included anatomical, inflammation, vascular malperfusion and villous maturation placental features. The secondary outcomes included fetal, maternal, perinatal and delivery complications. A multivariate analysis was conducted to adjust the results for factors potentially associated with placental pathology features. Results: A total of 1057 live births were included in the final analysis and were allocated to the study groups according to fetal gender: males ( n  = 527) and females ( n  = 530). After adjustment for potential confounding factors, male gender was significantly associated with villous agglutination (odds ratio [OR] 9.8; 95% confidence interval [CI] 1.4–78.2), avascular villi (OR 4.1; 95% CI 1.3–12.6) and maternal vascular malperfusion (OR 1.8; 95% CI 1.2–2.7). Female gender was significantly associated with bilobed placenta (OR 0.2; 95% CI 0.06–0.8) and subchorionic thrombi (OR 0.5; 95% CI 0.3–0.9). The prevalence of adverse fetal, maternal and delivery outcomes was similar between the groups. Conclusions: Newborn gender has a significant impact on the placental histopathology pattern, which can contribute to the development of adverse perinatal outcomes.